Microstructural characterization of nanocomposites produced by laser ablation in a magnetic field. (April 2020) - Nikov, Ru; Avdeev, G; Dikovska, A; Koleva, M; Nedyalkov, N
Abstract: We present a microstructural study of nanocomposite samples based on iron oxide and a noble or a transition metal. The samples were produced by laser ablation in air at atmospheric pressure in the presence of a magnetic field. This technology allows production of oriented nanowires composed by nanoparticles. We applied a simultaneous laser ablation of two targets in an external magnetic field. The targets used for the ablation were a magnetic material (iron) and a noble or a transition metal (silver, gold or cobalt). The presence of a magnetic field during the deposition results in arranging the nanoparticles formed in the plasma plume into micrometric nanowires on the substrate. The structural analyses confirms that the samples are composed by iron oxide and a noble or a transition metal.